Investigation of the role of the LC3 conjugation system in autophagy for human reward system reactivity - Treutlein, Jens; Krämer, Bernd; Gruber, Oliver (The world journal of biological psychiatry, 2025)
The dopaminergic reward system is involved in the aetiology of psychiatric disorders, and autophagy has been suggested to interfere with dopamine release. LC3 conjugation plays a key role in autophagy and comprises modification of autophagy protein LC3 with phosphatidylethanolamine. We investigated whether LC3 conjugation may influence the strength of activation in key regions of the mesolimbic reward system. To test our hypothesis, responses of the reward system to conditioned stimuli were assessed using the desire-reason dilemma (DRD) paradigm. Association of a set of missense variants with reward system responses was analysed in a sample of 214 healthy participants (mean age: 24.12 years; 128 females, 86 males). We detected association of the gene set with both ventral tegmental area (VTA) and nucleus accumbens (NAc) responses to conditioned reward stimuli (empirical P-values: R-VTA:0.008, R-NAc:0.009). The strongest missense variants were MAP1LC3B rs113610787 (p = 3.219e-05) for association with response in the L-NAc, and ATG4B rs143448469 (p = 4.366e-05) for the R-NAc. These exploratory results indicate that variation of the LC3 conjugation system influences responses of the VTA and NAc to conditioned reward stimuli. Further studies are required to replicate the findings and to investigate the possible role of LC3 conjugation in psychiatric disorders.